CAPITAL COST ANALYSIS USING THE WEIGHTED AVERAGE COST OF CAPITAL (WACC) METHOD AT PT. KALBE FARMA TBK - Yuliah Yuliah; Leni Triana; Ina Khadijah; Raden Irna Afriani (Yayasan Education and Social Center, 2023)
The cost of capital is a real cost that must be incurred by the company in obtaining funds from various sources. The cost of capital in this research uses the Weighted Average Cost of Capital (WACC) method which is the overall cost of the cost of capital and debt. This research was conducted at PT Kalbe Farma Tbk company for the 2018-2021 period. The WACC conditions for Tbk companies are optimal, in 2018-2020 the average weighted cost of capital has always decreased, 15.8%, 15.3%, 14.76%, 14.68% and experienced a non-significant increase of 0 .04%. A good WACC value is a value that provides the minimum rate of return required by investors in 2019-2020. This capital cost calculation can be used as a reference by company management to pay attention to the composition of debt and capital and can be taken into consideration by investors in investing their funds in the company